The Role Of Consumer Engagement, Preferences, And Opinions In Shaping The Market For Packaged Sambal Products - Elma Kania; Surya Setyawan (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
This study examines the role of consumer engagement, preferences, and opinions in shaping the market for packaged chili sauce products. Using a quantitative research approach and descriptive statistical analysis, data for this study was collected from the TikTokShop platform, with a focus on eatsambel brands. The findings indicate that consumer interests, perceptions, and actions have a significant and positive influence on the decision to purchase and provide valuable insights for marketers and businesses in the packaged chili sauce industry, emphasizing the importance of understanding the lifestyle aspects of consumers to better meet their needs and preference.